PEROXIDE TREATMENT IN EFFLORESCENCE PREVENTING - Jozefita Marku; Kozeta Vaso (Journal of Engineering & Processing Management, 2012)
Efflorescence is a crystalline deposit of water soluble salts on the surface of ceramic masonry. In most cases, efflorescence can be removed by various cleaning methods depending on the chemistry of the crystalline deposit. But this, sometimes, may even worse the problem. Therefore, it would be most desirable to minimize or to prevent the efflorescence through the proper selection of raw materials and by addition of appropriate admixtures and supplementary materials. Using clay with a high content of soluble salts, the aim of this experimental work was to evaluate the effect of H2O2 addition in efflorescence minimization. Some experiments are done using various concentrations of aqueous solutions of hydrogen peroxide. The oxidizing solutions are added to clay during various mixing times, prior to the forming stage. The content of the soluble salts in the fired clay specimens is evaluated qualitatively and quantitatively.
Keywords: peroxide; efflorescence; crystalline deposit; forming stage